Method for preparing cyclic carbonate by catalyzing epoxy compound and CO2 through nitrogen-doped carbon material
By using nitrogen-doped carbon material catalyst and combining with hydrothermal method to prepare the catalyst, the problem of difficult reuse of catalysts in the prior art and the need for cocatalysts is solved, and the efficient, environmentally friendly and economical conversion of CO2 into cyclic carbonate is achieved.
Patent Information
- Application Number
- CN202411758301.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-04-11
AI Technical Summary
In the prior art, when catalyzing the conversion of CO2 into cyclic carbonate, the catalyst is difficult to reuse, and a cocatalyst and halide ions are required, which affects environmental protection and economicality.
A catalyst with citric acid and urea as raw materials is prepared by hydrothermal method, combining suitable CO2 pressure, temperature and reaction time to achieve efficient conversion of CO2 and epoxy compounds.
Reusable catalysts are realized, the use of cocatalysts and halogen ions is avoided, cost and environmental pollution is reduced, and the yield of cyclic carbonate is improved.
Smart Images

Figure BDA0005166912730000111 
Figure BDA0005166912730000121 
Figure BDA0005166912730000131
Abstract
Description
Technical Field
[0001] The present invention relates to CO 2 The technical field of heterogeneous cycloaddition catalysts is a nitrogen-doped carbon material catalyzing the reaction of epoxy compounds with CO 2 Method for preparing cyclic carbonate Background Art
[0002] Since the Industrial Revolution, the massive use of fossil fuels has led to an increase in atmospheric CO 2 The content of CO has increased dramatically, causing many adverse effects on the global ecological environment. 2 Concentration has become an increasingly pressing issue. Currently, most research focuses on carbon capture and utilization. 2 It is a non-toxic, harmless, environmentally friendly and recyclable C1 resource. 2 The conversion of CO into various chemicals (methanol, formic acid, carbamate, organic carbonates, urea derivatives, inorganic carbonates, carboxylic acids) is also one of the hot topics in recent years. 2 The conversion into high value-added cyclic carbonates has the advantages of high atom economy, almost no by-products and environmental friendliness, so it has been widely studied. Cyclic carbonates are colorless, odorless, biodegradable organic compounds. It is a high value-added product with multiple uses. It can be used as an organic intermediate for the synthesis of non-alkyl polar solvents, polymer synthesis monomers, synthetic fibers, processing agents and pharmaceutical raw materials.
[0003] In the past few decades, people have developed a variety of catalysts such as MOF, carbon-based catalysts, ionic liquids, organic strong bases, hydrogen bond donor catalysts, and metal salt organic ligand complexes. Chinese invention patent application CN118598842A discloses a method for synthesizing cyclic carbonates by catalyzing the reaction of carbon dioxide and epoxy compounds with metal salt macrocyclic ligands. The method uses metal salt macrocyclic ligands as catalysts to catalyze the synthesis of cyclic carbonates from carbon dioxide and epoxy compounds; the complex formed by ferric chloride and Robson macrocyclic ligands in the presence of tetrabutylammonium bromide achieves a high yield of cyclic carbonates, but the catalytic system is homogeneous catalysis, and the catalyst is difficult to separate from the system by simple filtration or centrifugation, and has poor reusability.
[0004] Chinese invention patent CN114591284B discloses a method for the synthesis of CO based on Zn-MOF catalyst. 2 Method for synthesizing cyclic carbonate; the catalyst is composed of Zn-MOF and 1,3-bis(3,5-dimethylisophthalate)-1H-benzimidazolium bromide; the technology is used to catalyze CO under mild conditions 2The cycloaddition reaction with styrene oxide produces cyclic carbonate with a yield of more than 98%. However, this technology requires 1,3-bis(3,5-dimethylisophthalate)-1H-benzimidazolium bromide as a co-catalyst to have high catalytic activity. There is no catalyst for activating CO in the catalytic system. 2 Lewis base is needed, so halogen ions need to be added for the ring-opening reaction, but halogen ions are not environmentally friendly, and the co-catalyst needs to be added again each time during the cycle.
[0005] Recently, carbon-based catalysts have attracted widespread attention due to their abundant natural resources, high chemical stability and hydrothermal stability, controllable morphology and pores, and adjustable active sites. However, due to the lack of active sites, the ideal catalytic effect cannot be achieved, and doping elements is one of the commonly used modification methods. Researchers have obtained element-doped carbon materials by in situ doping or adding materials. Rajendra B. Mujmule et al. (Rajendra B. Mujmule, Wook-Jin Chung, Hern Kim. Chemical fixation of carbon dioxide catalyzed via hydroxyl and carboxyl-rich glucose carbonaceous material as a heterogeneous catalyst. Chemical Engineering Journal., 2020, 395, 25164) synthesized a series of glucose-based carbonaceous materials by hydrothermal method and successfully used them for CO 2 Cycloaddition reaction, but KI was used as a co-catalyst, which introduced halogen ions and had poor reusability. Anindya Ghosh et al. (Anindya Ghosh. Fabrication of a hollowsphere N,S co-doped bifunctional carbon catalyst for sustainable fixation of CO 2 to cyclic carbonates.Green Chem., 2022, 24, 1673) Hollow spherical N, S co-doped carbon materials were prepared using melamine and p-toluenesulfonic acid as nitrogen and sulfur precursors, and the efficient conversion of epichlorohydrin was successfully achieved. However, TBAI was used as a co-catalyst to introduce halogen ions, and the co-catalyst needed to be added again in the cyclic experiment. Summary of the invention
[0006] The purpose of the present invention is to provide an environmentally friendly, low-cost, catalyst-free, reusable catalyst for selectively catalyzing CO 2 A method for preparing high value-added cyclic carbonate chemicals from epoxy compounds.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] A nitrogen-doped carbon material catalyzes the reaction of epoxides with CO 2 The method for preparing cyclic carbonate comprises mixing a nitrogen-doped carbon material catalyst and an epoxy compound in a reactor, and controlling the CO 2 The pressure is 0.5-2 MPa, and the temperature is 110-150°C for 8-16 hours to react the epoxy compound and CO 2 Conversion to cyclic carbonates;
[0009] The carbon-based catalyst is prepared by the following method: citric acid, urea and DMF are mixed and fully dissolved, and placed in a high-pressure hydrothermal autoclave for hydrothermal reaction at a temperature of 180 to 240° C. for 6 to 12 hours; after the reaction is completed, it is cooled to room temperature, filtered, washed and dried; the molar ratio of citric acid to urea is 0.75 to 1.25:1.
[0010] In order to further achieve the purpose of the present invention, preferably, the mass ratio of the nitrogen-doped carbon material catalyst to the epoxy compound is 0.0042-0.083:1.
[0011] Preferably, the molar ratio of citric acid to urea is 0.75 to 1:1.
[0012] Preferably, the mass ratio of citric acid to DMF is 0.12-0.20:1.
[0013] Preferably, the filtration is performed by vacuum filtration using a Buchner funnel; and the washing is performed repeatedly using anhydrous ethanol.
[0014] Preferably, the drying is carried out in a vacuum drying oven.
[0015] Preferably, the drying is carried out at 60-80° C. for 12-16 hours.
[0016] Preferably, the epoxy compound is an epoxy compound containing a halogen electron-withdrawing group, an epoxy compound containing an electron-donating group and a large end group, and an epoxy compound containing a bicyclic ring.
[0017] Preferably, the epoxy compound containing a halogen electron-withdrawing group is one or more of epichlorohydrin, 2-(2-bromoethyl)ethylene oxide and epibromohydrin;
[0018] The epoxy compound containing an electron-donating group and a large end group is one or more of styrene oxide, 1,2-butylene oxide, 2-toluene glycidyl ether, glycidyl furfural ether, and allyl glycidyl ether;
[0019] The bicyclic epoxy compound is 1,4-butanediol diglycidyl ether.
[0020] Preferably, the nitrogen-doped carbon material catalyst after reacting at 110-150° C. for 8-16 hours is filtered, washed with anhydrous ethanol, and dried for reuse.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The citric acid and urea used in the present invention are cheap and readily available, and the catalyst can be obtained by a one-step hydrothermal method. The catalyst preparation cost is low, simple and efficient.
[0023] (2) The nitrogen-doped carbon material prepared by the present invention has high Lewis basicity and high molecular weight due to its high N (18%) and O (33.7%) doping content and the regulation of hydrothermal temperature and the molar ratio of citric acid and urea. Acidity enables efficient conversion of styrene oxide to styrene carbonate in the absence of solvents, metals, and halogen ions. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 C in Example 1 of the present invention 0.75 N 1 XRD pattern of -180 catalyst.
[0025] Figure 2 C in Example 1 of the present invention 0.75 N 1 -180 catalyst N 2 Physical adsorption-desorption isotherms.
[0026] Figure 3 C in Example 1 of the present invention 0.75 N 1 Pore size distribution diagram of -180 catalyst.
[0027] Figure 4 C in Example 1 of the present invention 0.75 N 1 SEM image of -180 catalyst.
[0028] Figure 5 C in Example 1 of the present invention 0.75 N 1 FT-IR spectrum of -180 catalyst.
[0029] Figure 6 C in Example 1 of the present invention 0.75 N 1 C1s spectrum in the XPS spectrum of -180 catalyst.
[0030] Figure 7 C in Example 1 of the present invention 0.75 N 1 O1s spectrum in the XPS spectrum of -180 catalyst.
[0031] Figure 8 C in Examples 1 to 6 of the present invention 0.75 N 1 -180, C 1 N 1 -180, C 1.25 N 1 N1s spectrum of -180 catalyst.
[0032] Fig. 9 C in Examples 1 to 6 of the present invention 0.75 N 1 -180, C 0.75 N 1 -200, C 0.75 N 1 -220, C 0.75 N 1 N1s spectrum of -240 catalyst.
[0033] Fig.10 C in Example 1 of the present invention 0.75 N 1 -180 catalyst for CO 2 -TPD spectrum.
[0034] Fig.11 The mass spectra of the products of styrene carbonate in Examples 7 to 22 of the present invention are shown in FIG. DETAILED DESCRIPTION
[0035] For a better understanding of the present invention, the present invention will be further described below with reference to the accompanying drawings and embodiments, but the embodiments of the present invention are not limited thereto.
[0036] The carbon-based catalyst of the present invention is prepared by the following method: citric acid, urea and DMF are mixed and fully dissolved, and placed in a high-pressure hydrothermal autoclave for hydrothermal reaction at 180-240°C for 6-12 hours; after the reaction is completed, it is cooled to room temperature, filtered, washed and dried; the molar ratio of citric acid to urea is 0.75-1.25:1. The carbon-based catalyst is represented by the following structural formula: C x N y -T, wherein x:y is the molar ratio of citric acid to urea, and T is the hydrothermal reaction temperature for catalyst preparation.
[0037] For the catalyst, the present invention found that by using highly functionalized citric acid with a low decomposition temperature as a carbon source and urea rich in N and with a low decomposition temperature as a nitrogen source, by changing the hydrothermal temperature and the molar ratio of citric acid to urea, the important properties of the catalyst such as acidity and alkalinity can be regulated, and high Lewis basicity and Acidity enables the reaction system of the present invention to efficiently convert styrene oxide into styrene carbonate in the absence of solvent, metal, and halogen ions to achieve CO 2 The high yield of cyclic carbonates is obtained by efficient conversion of epoxides. When the hydrothermal temperature is 180-240°C and the molar ratio of citric acid to urea is 0.75-1.25:1, the acidity and alkalinity of the catalyst reach the highest value at the same time, and the catalyst has a high yield of cyclic carbonates.
[0038] The present invention discloses a nitrogen-doped carbon material catalyzing the reaction of epoxy compounds with CO 2 A method for preparing a cyclic carbonate: mixing a nitrogen-doped carbon material catalyst and an epoxy compound in a reactor, controlling the CO 2 The pressure is 0.5-2 MPa, and the temperature is 110-150°C for 8-16 hours to react the epoxy compound and CO 2 Converted to cyclic carbonate.
[0039] Example 1: C 0.75 N 1 Preparation of -180 catalyst
[0040] Accurately weigh 75mmol of citric acid and 100mmol of urea and put them into the inner lining of the hydrothermal autoclave, add 125ml of DMF, grind the incompletely dissolved solid with a glass rod until it is completely dissolved, put it into the high-pressure hydrothermal autoclave and react at 180℃ for 12h. After the reaction is completed, cool it to room temperature, filter and wash it with anhydrous ethanol, and then put it into a vacuum drying oven at 80℃ for 12h to obtain C 0.75 N 1 -180 catalyst.
[0041] The prepared C 0.75 N 1 -180 was subjected to X-ray diffraction characterization to explore its crystal structure. The results are as follows Figure 1 As shown. There is a strong diffraction peak at 2θ = 26.6, which belongs to the graphene (002) plane, which is a typical case of graphite-like domains in amorphous carbon framework. There is a smaller diffraction peak at 2θ = 13.2, which may be caused by incomplete carbonization.
[0042] The prepared C 0.75 N 1 -180 for N2 Physical adsorption and desorption characterization was used to explore its pore structure. The results are as follows Figure 2 and Figure 3 As shown. Figure 2 It can be seen that C 0.75 N 1 The adsorption isotherm at -180° is a typical type IV isotherm and is within the high relative pressure range (P / P 0 =0.8~1.0) an obvious H4 type hysteresis loop can be observed, indicating that the carrier has a mesoporous structure. Figure 3 From the pore size distribution diagram, it can be seen that the main pore structure of the carrier is macropores of 50 to 100 nm, and contains a small amount of mesopores of 2 to 50 nm.
[0043] The prepared C 0.75 N 1 -180 was subjected to SEM characterization to explore its surface morphology. The results are as follows Figure 4 As shown in Figure 2, the catalyst exhibits a block structure with irregularly stacked nanosheets.
[0044] For the preparation of C 0.75 N 1 -180 for FT-IR characterization, the results are as follows Figure 5 As shown. Fourier transform infrared spectroscopy confirmed that after adding O element, a large number of oxygen-containing functional groups were generated on the catalyst surface. 3460cm -1 and 1758cm -1 The peaks at 3114cm belong to hydroxyl and carbonyl groups. In addition, the chemical bonds between carbon and nitrogen in the N-doped carbon structure are also supported by Fourier transform infrared spectroscopy. -1 and 1670cm -1 The peaks at belong to NH and C=N, respectively.
[0045] The prepared C 0.75 N 1 -180 was subjected to XPS characterization to explore the existence form of C elements on its surface. Figure 6 The C1s spectrum is shown in Figure 2. After peak separation, the deconvoluted peak C1s is mainly composed of four peaks at about 284.8, 286.1, 287.7, and 289.2, corresponding to CC / C=C, CO / CN, C=O, and -COOH, respectively, indicating that the addition of O element produces oxygen-containing functional groups such as carboxyl and hydroxyl groups, which can be used as hydrogen bond donors (HBD) for activated epoxy compounds.
[0046] The prepared C 0.75 N 1 -180 was subjected to XPS characterization to explore the existence form of O element on its surface. Figure 7The O1s spectrum is shown in Figure 2. After peak separation, the deconvoluted peak O1s consists of two peaks, located at about 531.4 and 533.2, corresponding to C=O and CO, respectively.
[0047] The prepared C 0.75 N 1 -180, C 1 N 1 -180, C 1.25 N 1 -180, C 0.75 N 1 -200, C 0.75 N 1 -220, C 0.75 N 1 -240 was subjected to XPS characterization to explore the existence form of N element on its surface. Figure 8 and Fig. 9 This is the N1s spectrum. After peak separation, it is shown that there are four nitrogen-containing components. The four peaks are roughly concentrated at 402.0-402.4, 400.6-401.0, 399.7-400.0, and 398.9-399.2, belonging to N-oxide, graphite-N, pyrrole-N, and pyridine-N, respectively. Semi-quantitative analysis of the N1s spectrum shows that C 0.75 N 1 -180 has the highest pyridine-N content, reaching 36.1%. As the catalyst preparation temperature increases, the pyridine-N content gradually decreases. 0.75 N 1 -240 has the lowest content of 19.7%, while the content of graphite-N increases from 18.3% to 30.4%, indicating that at high temperatures, graphite-N is more stable, pyridine-N will transform into graphite-N, and the catalyst will be more ordered, with fewer defects and higher crystallinity. This is consistent with the XRD results. As the carbon-nitrogen ratio increases, the change of N species is consistent with the temperature, pyridine-N decreases from 36.1% to 21%, and graphite-N increases from 18.3% to 31.2%.
[0048] The prepared C 0.75 N 1 -180 for CO 2 -TPD characterization to explore its alkalinity, the results are as follows Fig.10 As shown. Four CO can be observed in the low temperature zone (0-400℃), the medium and high temperature zone (400-600℃) and the high temperature zone (600-900℃). 2 The desorption peaks correspond to C 0.75 N 1 -180 weak base sites, medium strong base sites and strong base sites. There are more weak base sites, medium strong base sites and strong base sites in the table.
[0049] Example 2: C1 N 1 Preparation of -180 catalyst
[0050] Accurately weigh 100 mmol of citric acid and 100 mmol of urea and put them into the inner lining of the hydrothermal autoclave, add 125 ml of DMF, grind the incompletely dissolved solid with a glass rod until it is completely dissolved, put it into the high-pressure hydrothermal autoclave and react at 180°C for 12 hours. After the reaction is completed, cool it to room temperature, filter and wash it with anhydrous ethanol, and then put it into a vacuum drying oven at 80°C for 12 hours to obtain C 1 N 1 -180 catalyst.
[0051] Example 3: C 1.25 N 1 Preparation of -180 catalyst
[0052] Accurately weigh 125 mmol of citric acid and 100 mmol of urea and put them into the inner lining of the hydrothermal autoclave, add 125 ml of DMF, grind the incompletely dissolved solid with a glass rod until it is completely dissolved, put it into the high-pressure hydrothermal autoclave and react at 180°C for 12 hours. After the reaction is completed, cool it to room temperature, filter and wash it with anhydrous ethanol, and then put it into a vacuum drying oven at 80°C for 12 hours to obtain C 1.25 N 1 -180 catalyst.
[0053] Example 4: C 0.75 N 1 Preparation of -200 catalyst
[0054] Accurately weigh 75mmol of citric acid and 100mmol of urea and put them into the inner lining of the hydrothermal autoclave, add 125ml of DMF, grind the incompletely dissolved solid with a glass rod until it is completely dissolved, put it into the high-pressure hydrothermal autoclave and react at 200℃ for 12h. After the reaction is completed, cool it to room temperature, filter and wash it with anhydrous ethanol, and then put it into a vacuum drying oven at 80℃ for 12h to obtain C 0.75 N 1 -200 catalyst.
[0055] Example 5: C 0.75 N 1 Preparation of -220 catalyst
[0056] Accurately weigh 75mmol of citric acid and 100mmol of urea and put them into the inner lining of the hydrothermal autoclave, add 125ml of DMF, grind the incompletely dissolved solid with a glass rod until it is completely dissolved, put it into the high-pressure hydrothermal autoclave and react at 220℃ for 12h. After the reaction is completed, cool it to room temperature, filter and wash it with anhydrous ethanol, and then put it into a vacuum drying oven at 80℃ for 12h to obtain C 0.75 N1 -220 catalyst.
[0057] Example 6: C 0.75 N 1 Preparation of -240 catalyst
[0058] Accurately weigh 75mmol of citric acid and 100mmol of urea and put them into the inner lining of the hydrothermal autoclave, add 125ml of DMF, grind the incompletely dissolved solid with a glass rod until it is completely dissolved, put it into the high-pressure hydrothermal autoclave and react at 240℃ for 12h. After the reaction is completed, cool it to room temperature, filter and wash it with anhydrous ethanol, and then put it into a vacuum drying oven at 80℃ for 12h to obtain C 0.75 N 1 -240 catalyst.
[0059] Example 7: C 0.75 N 1 -180 Catalytic CO 2 Cycloaddition reaction
[0060] Weigh 10 mmol of styrene oxide, 100 mg of C 0.75 N 1 -180 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO 2 Replace the air in the kettle three times and fill it with 1.0MPa CO 2 , react at 130°C for 12h. After the reaction is completed and cooled to room temperature, the reaction solution is taken out and internal standard biphenyl is added, and 1mL of the reaction solution is taken out for analysis by GC-MS-FID.
[0061] The calculation results show that the conversion rate of styrene oxide is 97% and the yield of styrene carbonate is 66.1%.
[0062] Fig.11 The mass spectra of the products of Examples 7 to 22 are basically consistent with the mass spectra of standard styrene carbonate, which indicates that the obtained products are styrene carbonate.
[0063] Example 8: C 1 N 1 -180 Catalytic CO 2 Cycloaddition reaction
[0064] The difference between this embodiment and implementation example 7 is that:
[0065] Weigh 10 mmol of styrene oxide, 100 mg of C 1 N 1 -180 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO 2 Replace the air in the kettle three times and fill it with 1.0MPa CO2 , react at 130°C for 12h. After the reaction is completed and cooled to room temperature, the reaction solution is taken out and internal standard biphenyl is added, and 1mL of the reaction solution is taken out for analysis by GC-MS-FID.
[0066] The calculation results show that the conversion rate of styrene oxide is 64.8%, and the yield of styrene carbonate is 35.3%.
[0067] Example 9: C 1.25 N 1 -180 Catalytic CO 2 Cycloaddition reaction
[0068] The difference between this embodiment and implementation example 7 is that:
[0069] Weigh 10 mmol of styrene oxide, 100 mg of C 1.25 N 1 -180 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO 2 Replace the air in the kettle three times and fill it with 1.0MPa CO 2 , react at 130°C for 12h. After the reaction is completed and cooled to room temperature, the reaction solution is taken out and internal standard biphenyl is added, and 1mL of the reaction solution is taken out for analysis by GC-MS-FID.
[0070] The calculation results show that the conversion rate of styrene oxide is 57.1%, and the yield of styrene carbonate is 20.5%.
[0071] Example 10: C 0.75 N 1 -200 Catalytic CO 2 Cycloaddition reaction
[0072] The difference between this embodiment and implementation example 7 is that:
[0073] Weigh 10 mmol of styrene oxide, 100 mg of C 0.75 N 1 -200 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO 2 Replace the air in the kettle three times and fill it with 1.0MPa CO 2 , react at 130°C for 12h. After the reaction is completed and cooled to room temperature, the reaction solution is taken out and internal standard biphenyl is added, and 1mL of the reaction solution is taken out for analysis by GC-MS-FID.
[0074] The calculation results show that the conversion rate of styrene oxide is 96%, and the yield of styrene carbonate is 62.9%.
[0075] Example 11: C 0.75 N 1-220 catalytic CO 2 Cycloaddition reaction
[0076] The difference between this embodiment and implementation example 7 is that:
[0077] Weigh 10 mmol of styrene oxide, 100 mg of C 0.75 N 1 -220 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO 2 Replace the air in the kettle three times and fill it with 1.0MPa CO 2 , react at 130°C for 12h. After the reaction is completed and cooled to room temperature, the reaction solution is taken out and internal standard biphenyl is added, and 1mL of the reaction solution is taken out for analysis by GC-MS-FID.
[0078] The calculation results show that the conversion rate of styrene oxide is 84.1%, and the yield of styrene carbonate is 56.6%.
[0079] Example 12: C 0.75 N 1 -240 catalytic CO 2 Cycloaddition reaction
[0080] The difference between this embodiment and implementation example 7 is that:
[0081] Weigh 10 mmol of styrene oxide, 100 mg of C 0.75 N 1 -240 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO 2 Replace the air in the kettle three times and fill it with 1.0MPa CO 2 , react at 130°C for 12h. After the reaction is completed and cooled to room temperature, the reaction solution is taken out and internal standard biphenyl is added, and 1mL of the reaction solution is taken out for analysis by GC-MS-FID.
[0082] The calculation results show that the conversion rate of styrene oxide is 62.4% and the yield of styrene carbonate is 51%.
[0083] Example 13: C 0.75 N 1 -180 Catalytic CO 2 Cycloaddition reaction
[0084] Weigh 10 mmol of styrene oxide, 25 mg of C 0.75 N 1 -180 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO 2 Replace the air in the kettle three times and fill it with 1.0MPa CO 2, react at 130°C for 12h. After the reaction is completed and cooled to room temperature, the reaction solution is taken out and internal standard biphenyl is added, and 1mL of the reaction solution is taken out for analysis by GC-MS-FID.
[0085] The calculation results show that the conversion rate of styrene oxide is 88.5%, and the yield of styrene carbonate is 81.5%.
[0086] Example 14: C 0.75 N 1 -180 Catalytic CO 2 Cycloaddition reaction
[0087] Weigh 10 mmol of styrene oxide, 5 mg of C 0.75 N 1 -180 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO 2 Replace the air in the kettle three times and fill it with 1.0MPa CO 2 , react at 130°C for 12h. After the reaction is completed and cooled to room temperature, the reaction solution is taken out and internal standard biphenyl is added, and 1mL of the reaction solution is taken out for analysis by GC-MS-FID.
[0088] The calculation results show that the conversion rate of styrene oxide is 47.3%, and the yield of styrene carbonate is 40.2%.
[0089] Example 15: C 0.75 N 1 -180 Catalytic CO 2 Cycloaddition reaction
[0090] Weigh 10 mmol of styrene oxide, 50 mg of C 0.75 N 1 -180 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO 2 Replace the air in the kettle three times and fill it with 1.0MPa CO 2 , react at 130°C for 12h. After the reaction is completed and cooled to room temperature, the reaction solution is taken out and internal standard biphenyl is added, and 1mL of the reaction solution is taken out for analysis by GC-MS-FID.
[0091] The calculation results show that the conversion rate of styrene oxide is 93.5%, and the yield of styrene carbonate is 80%.
[0092] Example 16: C 0.75 N 1 -180 Catalytic CO 2 Cycloaddition reaction
[0093] Weigh 10 mmol of styrene oxide, 25 mg of C 0.75 N 1-180 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO 2 Replace the air in the kettle three times and fill it with 0.5MPa CO 2 , react at 130°C for 12h. After the reaction is completed and cooled to room temperature, the reaction solution is taken out and internal standard biphenyl is added, and 1mL of the reaction solution is taken out for analysis by GC-MS-FID.
[0094] The calculation results show that the conversion rate of styrene oxide is 84.2%, and the yield of styrene carbonate is 74.1%.
[0095] Example 17: C 0.75 N 1 -180 Catalytic CO 2 Cycloaddition reaction
[0096] Weigh 10 mmol of styrene oxide, 25 mg of C 0.75 N 1 -180 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO 2 Replace the air in the kettle three times and fill it with 2.0MPa CO 2 , react at 130°C for 12h. After the reaction is completed and cooled to room temperature, the reaction solution is taken out and internal standard biphenyl is added, and 1mL of the reaction solution is taken out for analysis by GC-MS-FID.
[0097] The calculation results show that the conversion rate of styrene oxide is 84.2% and the yield of styrene carbonate is 72.9%.
[0098] Example 18: C 0.75 N 1 -180 Catalytic CO 2 Cycloaddition reaction
[0099] Weigh 10 mmol of styrene oxide, 25 mg of C 0.75 N 1 -180 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO 2 Replace the air in the kettle three times and fill it with 1.0MPa CO 2 , react at 140°C for 12h. After the reaction is completed and cooled to room temperature, the reaction solution is taken out and added with internal standard biphenyl, and 1mL of the reaction solution is taken out for analysis by GC-MS-FID.
[0100] The calculation results show that the conversion rate of styrene oxide is 95%, and the yield of styrene carbonate is 76.2%.
[0101] Example 19: C 0.75 N 1 -180 Catalytic CO 2 Cycloaddition reaction
[0102] Weigh 10 mmol of styrene oxide, 25 mg of C 0.75 N 1 -180 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO 2 Replace the air in the kettle three times and fill it with 1.0MPa CO 2 , react at 150°C for 12h. After the reaction is completed and cooled to room temperature, the reaction solution is taken out and internal standard biphenyl is added, and 1mL of the reaction solution is taken out for analysis by GC-MS-FID.
[0103] The calculation results show that the conversion rate of styrene oxide is 96.2%, and the yield of styrene carbonate is 73.6%.
[0104] Example 20: C 0.75 N 1 -180 Catalytic CO 2 Cycloaddition reaction
[0105] Weigh 10 mmol of styrene oxide, 25 mg of C 0.75 N 1 -180 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO 2 Replace the air in the kettle three times and fill it with 1.0MPa CO 2 , react at 130°C for 8h. After the reaction is completed and cooled to room temperature, the reaction solution is taken out and internal standard biphenyl is added, and 1 mL of the reaction solution is taken out for analysis by GC-MS-FID.
[0106] The calculation results show that the conversion rate of styrene oxide is 55%, and the yield of styrene carbonate is 49.7%.
[0107] Example 21: C 0.75 N 1 -180 Catalytic CO 2 Cycloaddition reaction
[0108] Weigh 10 mmol of styrene oxide, 25 mg of C 0.75 N 1 -180 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO 2 Replace the air in the kettle three times and fill it with 1.0MPa CO 2 , react at 130°C for 10 hours. After the reaction is completed and cooled to room temperature, the reaction solution is taken out and internal standard biphenyl is added, and 1 mL of the reaction solution is taken out for analysis by GC-MS-FID.
[0109] The calculation results show that the conversion rate of styrene oxide is 65.3%, and the yield of styrene carbonate is 60.7%.
[0110] Example 22: C 0.75 N 1 -180 Catalytic CO 2 Cycloaddition reaction
[0111] Weigh 10 mmol of styrene oxide, 25 mg of C 0.75 N 1 -180 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO 2 Replace the air in the kettle three times and fill it with 1.0MPa CO 2 , react at 130°C for 16h. After the reaction was completed and cooled to room temperature, the reaction solution was taken out and added with internal standard biphenyl, and 1mL of the reaction solution was analyzed by GC-MS-FID.
[0112] The calculation results show that the conversion rate of styrene oxide is 95.6%, and the yield of styrene carbonate is 78.4%.
[0113] Example 23: C 0.75 N 1 -180 Catalytic CO 2 Cycloaddition reaction
[0114] Weigh 10mmol epichlorohydrin, 25mg C 0.75 N 1 -180 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO 2 Replace the air in the kettle three times and fill it with 1.0MPa CO 2 , react at 130°C for 12h. After the reaction is completed and cooled to room temperature, the reaction solution is taken out and internal standard biphenyl is added, and 1mL of the reaction solution is taken out for analysis by GC-MS-FID.
[0115] The calculation results show that the conversion rate of epichlorohydrin is 99.7% and the yield of cyclic carbonate is 95%.
[0116] Example 24: C 0.75 N 1 -180 Catalytic CO 2 Cycloaddition reaction
[0117] Weigh 10mmol of epibromopropane, 25mg of C 0.75 N 1 -180 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO 2 Replace the air in the kettle three times and fill it with 1.0MPa CO 2 , react at 130°C for 12h. After the reaction is completed and cooled to room temperature, the reaction solution is taken out and internal standard biphenyl is added, and 1mL of the reaction solution is taken out for analysis by GC-MS-FID.
[0118] The calculation results show that the conversion rate of epibromohydrin is 99.7% and the yield of cyclic carbonate is 97%.
[0119] Example 25: C 0.75 N 1 -180 Catalytic CO 2 Cycloaddition reaction
[0120] Weigh 10 mmol of 2-(2-bromoethyl)ethylene oxide, 25 mg of C 0.75 N 1 -180 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO 2 Replace the air in the kettle three times and fill it with 1.0MPa CO 2 , react at 130°C for 12h. After the reaction is completed and cooled to room temperature, the reaction solution is taken out and internal standard biphenyl is added, and 1mL of the reaction solution is taken out for analysis by GC-MS-FID.
[0121] The calculation results show that the conversion rate of 2-(2-bromoethyl)oxirane is 86.6%, and the yield of cyclic carbonate is 72.2%.
[0122] Example 26: C 0.75 N 1 -180 Catalytic CO 2 Cycloaddition reaction
[0123] Weigh 10 mmol 1,2-butylene oxide, 100 mg C 0.75 N 1 -180 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO 2 Replace the air in the kettle three times and fill it with 1.0MPa CO 2 , react at 130°C for 12h. After the reaction is completed and cooled to room temperature, the reaction solution is taken out and internal standard biphenyl is added, and 1mL of the reaction solution is taken out for analysis by GC-MS-FID.
[0124] The calculation results show that the conversion rate of 1,2-butylene oxide is 86.6% and the yield of cyclic carbonate is 72.2%.
[0125] Example 27: C 0.75 N 1 -180 Catalytic CO 2 Cycloaddition reaction
[0126] Weigh 10 mmol of glycidyl furfural, 50 mg of C 0.75 N 1 -180 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO2 Replace the air in the kettle three times and fill it with 1.0MPa CO 2 , react at 130°C for 12h. After the reaction is completed and cooled to room temperature, the reaction solution is taken out and internal standard biphenyl is added, and 1mL of the reaction solution is taken out for analysis by GC-MS-FID.
[0127] The calculation results show that the conversion rate of glycidyl furfuryl ether is 94% and the yield of cyclic carbonate is 89.3%.
[0128] Example 28: C 0.75 N 1 -180 Catalytic CO 2 Cycloaddition reaction
[0129] Weigh 10 mmol of allyl glycidyl ether, 100 mg of C 0.75 N 1 -180 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO 2 Replace the air in the kettle three times and fill it with 1.0MPa CO 2 , react at 130°C for 12h. After the reaction is completed and cooled to room temperature, the reaction solution is taken out and internal standard biphenyl is added, and 1mL of the reaction solution is taken out for analysis by GC-MS-FID.
[0130] The calculation results show that the conversion rate of allyl glycidyl ether is 88.7% and the yield of cyclic carbonate is 81%.
[0131] Example 29: C 0.75 N 1 -180 Catalytic CO 2 Cycloaddition reaction
[0132] Weigh 10 mmol of glycidyl phenyl ether, 50 mg of C 0.75 N 1 -180 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO 2 Replace the air in the kettle three times and fill it with 1.0MPa CO 2 , react at 130°C for 12h. After the reaction is completed and cooled to room temperature, the reaction solution is taken out and internal standard biphenyl is added, and 1mL of the reaction solution is taken out for analysis by GC-MS-FID.
[0133] The calculation results show that the conversion rate of glycidyl phenyl ether is 86.2%, and the yield of cyclic carbonate is 82%.
[0134] Example 30: C 0.75 N 1 -180 Catalytic CO 2 Cycloaddition reaction
[0135] Weigh 10 mmol 2-toluene glycidyl ether, 100 mg C 0.75 N 1 -180 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO 2 Replace the air in the kettle three times and fill it with 1.0MPa CO 2 , react at 130°C for 12h. After the reaction is completed and cooled to room temperature, the reaction solution is taken out and internal standard biphenyl is added, and 1mL of the reaction solution is taken out for analysis by GC-MS-FID.
[0136] The calculation results show that the conversion rate of 2-toluene glycidyl ether is 98%, and the yield of cyclic carbonate is 88.6%.
[0137] Example 31: C 0.75 N 1 -180 Catalytic CO 2 Cycloaddition reaction
[0138] Weigh 10 mmol 1,4-butanediol diglycidyl ether, 100 mg C 0.75 N 1 -180 catalyst in a 35mL reactor. The reactor was sealed and high-purity CO 2 Replace the air in the kettle three times and fill it with 1.0MPa CO 2 , react at 130°C for 12h. After the reaction is completed and cooled to room temperature, the reaction solution is taken out and internal standard biphenyl is added, and 1mL of the reaction solution is taken out for analysis by GC-MS-FID.
[0139] The calculation results show that the conversion rate of 1,4-butanediol diglycidyl ether is 95.4% and the yield of cyclic carbonate is 79.8%.
[0140] Table 1 Synthesis of cyclic carbonates by cycloaddition reaction of different epoxides
[0141]
[0142]
[0143] As can be seen from Table 1, for epoxy compounds containing electron-withdrawing groups such as halogen (23, 24, 26), since the electron-withdrawing groups are conducive to the ring-opening reaction, a higher yield can be obtained when the catalyst dosage remains unchanged, and the yields of epichlorohydrin and epibromohydrin exceed 95%. For epoxy compounds containing electron-donating groups and large end groups (25, 27, 28, 29, 30), due to the influence of electronic and steric hindrance effects, a good yield of more than 80% can still be obtained after appropriately increasing the catalyst dosage; for epoxy compounds containing bicyclic rings (31), a yield of more than 80% can also be obtained after appropriately increasing the catalyst dosage. Therefore, it can be concluded that C 0.75 N 1 -180 has good substrate applicability.
[0144] Example 33: C 0.75 N 1 -180 catalyst recycling performance
[0145] Taking the catalytic cycloaddition reaction of epichlorohydrin as an example, the catalytic reaction conditions remain unchanged. After the reaction is completed, the solid catalyst is separated by filtration, and the catalyst is subjected to catalytic reaction again under the same reaction conditions. The catalytic results are shown in Table 2. The results show that the activity of the catalyst decreases slightly after 5 cycles, but the conversion rate is still as high as 90%, and the yield is more than 88%, indicating that it has good recycling performance. Compared with CN118598842A and CN114591284B, the catalyst can be simply filtered and reused, and no external co-catalyst or halogen ion is required to assist the ring-opening reaction. C prepared by hydrothermal reaction 0.75 N 1 -180 has high nitrogen and oxygen doping content, as shown by XPS and CO 2 -TPD shows that the catalyst has high Lewis basicity and Acidic, can better activate CO 2 and epoxides, thereby achieving efficient catalytic cycloaddition reactions under halogen-free conditions.
[0146] It can be seen from the above examples that the present invention uses a nitrogen-doped carbon material catalytic system to achieve CO 2 Cycloaddition reaction, when the catalyst dosage is 5-100 mg, CO 2 Under the conditions of pressure of 5 to 20 bar, reaction temperature of 110 to 150° C., and reaction time of 8 to 16 hours, the conversion rate of styrene oxide is 47.3 to 97%, and the yield of styrene carbonate is 40.2 to 81.5%. The nitrogen-doped carbon material catalyst used in the present invention has low cost, simple preparation process, low environmental pollution, is conducive to reducing energy consumption, and achieves a high yield of cyclic carbonate under relatively mild conditions.
[0147] Table 2 Catalyst recycling effect
[0148]
[0149] The implementation methods of the present invention are not limited to the above-mentioned embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. A method for preparing cyclic carbonate by catalyzing epoxide and CO2 using nitrogen-doped carbon materials, characterized in that: The nitrogen-doped carbon material catalyst and the epoxide compound are mixed in a reactor, the CO2 pressure in the reactor is controlled to be 0.5-2 MPa, and the reaction is carried out at a temperature of 110-150° C. for 8-16 hours to convert the epoxide compound and CO2 into cyclic carbonate; The carbon-based catalyst is prepared by the following method: citric acid, urea and DMF are mixed and fully dissolved, and placed in a high-pressure hydrothermal autoclave for hydrothermal reaction at a temperature of 180 to 240° C. for 6 to 12 hours; after the reaction is completed, it is cooled to room temperature, filtered, washed and dried; the molar ratio of citric acid to urea is 0.75 to 1.25:
1.
2. The method for preparing cyclic carbonate by catalyzing epoxy compounds and CO2 using nitrogen-doped carbon materials according to claim 1, characterized in that: The mass ratio of the nitrogen-doped carbon material catalyst to the epoxy compound is 0.0042-0.083:
1.
3. The method for preparing cyclic carbonate by catalyzing epoxy compounds and CO2 using nitrogen-doped carbon materials according to claim 1, characterized in that: The molar ratio of the citric acid to the urea is 0.75-1:
1.
4. The method for preparing cyclic carbonate by catalyzing epoxy compounds and CO2 using nitrogen-doped carbon materials according to claim 1, characterized in that: The mass ratio of the citric acid to DMF is 0.12-0.20:
1.
5. The method for preparing cyclic carbonate by catalyzing epoxy compounds and CO2 using nitrogen-doped carbon materials according to claim 1, characterized in that: The filtering is performed by using a Buchner funnel to perform reduced pressure filtering; and the washing is performed by repeatedly washing with anhydrous ethanol.
6. The method for preparing cyclic carbonate by catalyzing epoxy compounds and CO2 using nitrogen-doped carbon materials according to claim 1, characterized in that: The drying is carried out in a vacuum drying oven.
7. The method for preparing cyclic carbonate by catalyzing epoxy compounds and CO2 using nitrogen-doped carbon materials according to claim 6, characterized in that: The drying is carried out at 60-80°C for 12-16 hours.
8. The method for preparing cyclic carbonate by catalyzing epoxy compounds and CO2 using nitrogen-doped carbon materials according to claim 1, characterized in that: The epoxy compound is an epoxy compound containing a halogen electron-withdrawing group, an epoxy compound containing an electron-donating group and a large end group, and an epoxy compound containing a bicyclic ring.
9. The method for preparing cyclic carbonate by catalyzing epoxy compounds and CO2 using nitrogen-doped carbon materials according to claim 1, characterized in that: The epoxy compound containing a halogen electron-withdrawing group is one or more of epichlorohydrin, 2-(2-bromoethyl)ethylene oxide and epibromohydrin; The epoxy compound containing an electron-donating group and a large end group is one or more of styrene oxide, 1,2-butylene oxide, 2-toluene glycidyl ether, glycidyl furfural ether, and allyl glycidyl ether; The bicyclic epoxy compound is 1,4-butanediol diglycidyl ether.
10. The method for preparing cyclic carbonate by catalyzing epoxy compounds and CO2 using nitrogen-doped carbon materials according to claim 1, characterized in that: The nitrogen-doped carbon material catalyst reacted at 110-150° C. for 8-16 hours is filtered, washed with anhydrous ethanol, dried and reused.
Citation Information
Patent Citations
A method for synthesizing cyclic carbonates in CO2 based on a Zn-MOF catalyst
CN114591284B
Method for synthesizing cyclic carbonate from carbon dioxide and epoxide under catalysis of metal salt macrocyclic ligand
CN118598842A